2020
DOI: 10.5010/jpb.2020.47.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of triple recessive alleles for three antinutritional proteins in soybean with black seed coat and green cotyledon

Abstract: The black seed coat of soybeans contain anthocyanins which promote health. However, mature soybean seeds contain anti-nutritional factors like lipoxygenase, lectin and Kunitz Trypsin Inhibitor (KTI) proteins. Furthermore, these seeds can be used only after the genetic elimination of these proteins. Therefore, the objective of this study was to develop novel soybean genotypes with black seed coat and triple recessive alleles (lx1lx1lx2lx2lx3lx3, titilele) for lipoxygenase, lectin, and KTI proteins. From a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, globally development of specialty soybean free from KTI and lipoxygenases is the major objective in quality improvement of soybean. In Korea, Lee et al ., (2014) developed triple null lipoxygenase mutant line ‘H70’ by irradiating cultivar ‘Hwanggum’ with gamma rays (250 Gy), while Kang et al ., (2020) reported a black soybean line free from lipoxygenases, KTI and lectin through conventional breeding using four parents ‘Gaechuck#1’ (Lox2, Lox3 and KTI free), ‘Jimpum#2’ (Lox1, Lox2, Lox3 and KTI free), ‘12N1’ (Lox1, Lox2, Lox3 and KTI free) and ‘Le-16’ (lectin free). In China, Wang et al ., (2020) developed triple null lipoxygenase lines, ‘GmLox-28’ and ‘GmLox-60’ using CRISPR-associated protein 9 strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, globally development of specialty soybean free from KTI and lipoxygenases is the major objective in quality improvement of soybean. In Korea, Lee et al ., (2014) developed triple null lipoxygenase mutant line ‘H70’ by irradiating cultivar ‘Hwanggum’ with gamma rays (250 Gy), while Kang et al ., (2020) reported a black soybean line free from lipoxygenases, KTI and lectin through conventional breeding using four parents ‘Gaechuck#1’ (Lox2, Lox3 and KTI free), ‘Jimpum#2’ (Lox1, Lox2, Lox3 and KTI free), ‘12N1’ (Lox1, Lox2, Lox3 and KTI free) and ‘Le-16’ (lectin free). In China, Wang et al ., (2020) developed triple null lipoxygenase lines, ‘GmLox-28’ and ‘GmLox-60’ using CRISPR-associated protein 9 strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Two germplasms (Gaechuck#1 and PI567476) were used for selection of the novel soybean line with a black seed coat, a green cotyledon, and the lox2lox2lox3lox3-titi-p34p34 genotype. Using the lox2lox2lox3lox3-titi-p34p34 genotype as well as previously reported soybean lines (Choi et al 2016;Kang et al 2020), a novel parent 2(P2) was obtained. The traits for the components, including lectin, KTI, P34, lipoxygenase, and stachyose for the novel parent 1(P1, Choi et al 2021), novel parent 2(P2), Gaechuck#1 and PI567476 are shown in Table 1.…”
Section: Breeding Population and Schemementioning
confidence: 99%
“…Therefore, breeding of soybean varieties that are genetically devoid of these components is needed. To date, some studies have reported on the breeding of lines with a black seed coat and a green cotyledon with the lele-titi genotype (Choi et al 2016), lines with the titi-rs2rs2 genotype (Choi et al 2019), lines with the lele-titi-cgy1cgy1 genotype (Kang et al 2020), and lines with the lele-titi-lox1lox1lox2lox2lox3lox3-cgy1cgy1 genotype (choi et al 2021). However, no studies have reported on lines with a black seed coat and a green cotyledon recessive for all ve components of lectin, KTI, P34, lipoxygenase, and stachyose.…”
Section: Introductionmentioning
confidence: 99%